EFFECTIVE METHODS FOR TEACHING PEDIATRIC PARENTERAL NUTRITION TO MEDICAL STUDENTS (World Bulletin of Public Health, 2024)
Pediatric parenteral nutrition (PN) is a complex and essential aspect of pediatric healthcare, requiring medical students to gain in-depth knowledge and hands-on skills for its effective application. Teaching this topic poses unique challenges due to the technical intricacies, ethical considerations, and critical decision-making involved. This article explores effective teaching methods for pediatric PN, integrating active learning strategies, technologyenhanced education, and case-based simulations to optimize student comprehension and skill acquisition. By examining a variety of pedagogical approaches, including flipped classrooms, e-learning modules, and interprofessional collaboration, the study highlights best practices in educating future medical professionals. Special emphasis is placed on using simulation-based learning and case studies to bridge the gap between theoretical knowledge and clinical practice. The article concludes with recommendations for developing a robust curriculum that combines traditional and innovative teaching techniques, ensuring that medical students are well-prepared to manage pediatric PN in their future careers.
Keywords: pediatric parenteral nutrition; medical education; active learning